Low skeletal muscle mass is associated with insulin resistance, diabetes, and metabolic syndrome in the Korean population: The Korea National Health and Nutrition Examination Survey (KNHANES) 2009-2010 - Moon, Seong-Su (Endocrine Journal, 2014)
Sarcopenia is an emerging risk factor for metabolic disorders. No study of the association of sarcopenia with insulin resistance, diabetes, and metabolic syndrome (MS) according to age group and obesity status in the general population has been reported. We investigated these associations in the Korean population. Participants included 4558 males and 5874 females, who were ≥20 years of age or older from the fourth and fifth Korea National Health and Nutritional Examination Surveys of the Korean population (2009 and 2010). Age was categorized according to three groups (20-39, 40-59, and ≥ 60 years). Obesity was defined according to body mass index. Sarcopenia was defined as the appendicular skeletal muscle mass (ASM) divided by weight (Wt) (%) of > 2SD below the sex-specific mean for young adults. Homeostasis model assessment of insulin resistance (HOMA-IR) was calculated. After adjustment for confounding variables, sarcopenia showed a significant association with HOMA-IR in the non-obese group (P<0.001). Sarcopenia was found to be a risk factor for diabetes in the non-obese group (OR, 2.140; 95% CI, 1.549-2.956; P<0.001). Sarcopenia also showed an association with MS in the non-obese group (OR, 2.209; 95% CI, 1.679-2.906; P<0.001), but not in the obese-group. However, these results were not relevant to young age group. In conclusion, sarcopenia showed an association with insulin resistance, diabetes, and MS, in the non-obese population. Sarcopenia may be an early predictor for diabetes and MS susceptibility in the non-obese population, particularly in elderly people.